2007
DOI: 10.1111/j.1524-4741.2007.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Delaying Adjuvant Radiation Treatment after Conservative Surgery for Early Breast Cancer

Abstract: n Abstract: We examined the effect of delaying radiation treatment after conservative surgery on the risk of breast cancer local recurrence (LR). From January 1997 to December 2001, 969 women with early-stage breast cancer were treated at the Radiation Oncology Department in Chieti. We analyzed 802 of them who underwent conservative surgery followed by whole-breast radiotherapy. The patients were divided into two groups: women who did not receive chemotherapy and women who received chemotherapy. The time inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
(24 reference statements)
1
24
0
Order By: Relevance
“…The impact of the TI from surgery to adjuvant therapy (radiation or concurrent chemoradiation) has been studied mainly in breast, endometrial, and head and neck cancers [101112132223]. Several retrospective cohort studies have found that a longer TI is associated with poor oncological outcomes of these cancers [10111222].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of the TI from surgery to adjuvant therapy (radiation or concurrent chemoradiation) has been studied mainly in breast, endometrial, and head and neck cancers [101112132223]. Several retrospective cohort studies have found that a longer TI is associated with poor oncological outcomes of these cancers [10111222].…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of TI from surgery to the beginning of adjuvant therapy on oncological outcomes were not demonstrated by previous studies [1315]. A study by Cèfaro et al [13] examined the effect of delaying RT after conservative surgery on the risk of local recurrence in 969 women with early stage breast cancer, and found that the TI from surgery to RT was not associated with local recurrence. The reason for the discrepancy is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive margin, the presence of disease on the inked surface, occurs in at least 30-35% of cases, and an additional 10-15% are classified as close margins (< 2 mm)(15). Local recurrence rates for breast conserving therapy followed by radiation were reported in 2-28% of cases with positive margins, 2-16% with close margins (<2 mm), and 2-8% with negative margins (15) which would be higher in the absence of radiation therapy (6, 8, 17, 18). …”
Section: Introductionmentioning
confidence: 99%
“…Long wait criteria for adjuvant RT were six (node negative disease) or seven months (node positive disease) postsurgery if RT was preceded by CT, four months if it was not. 15,[42][43][44][45][46] These previous studies suggested that such waits, comprised of systemic delays and necessary waiting (investigations, preparation for treatment and post-surgical recovery periods) may be associated with disease recurrence, metastases and shorter survival. This study's descriptive epidemiologic analyses will allow for the practical empirical planning of future multivariate analyses of the relationships between breast cancer care waits and survival in Canada and the United States.…”
mentioning
confidence: 99%